Care of Non COVID Patients in COVID-19 Era - Piryani, S.; Piryani, R.M.; Dangal, G. (Kathmandu University Medical Journal, 2020)
The consequences of the COVID-19 pandemic are extensive and far-reaching. Non COVID communicable diseases continue to spread and non-communicable diseases continue to progress. People may access healthcare facilities little bit late due to fear of contracting COVID-19 and present with severe symptoms, even with complications. Nepal has been facing dual burden of both non-communicable and communicable diseases. The number of COVID-19 patients has continuously been rising in Nepal since the start of May 2020. There is an anticipated surge of infectious disease such as malaria, dengue fever, enteric fever, scrub typhus, leptospirosis during summer and monsoon seasons in Nepal. There will be surge of cases of acute undifferentiated febrile illness (AUFI) during monsoon. As fever is one of the very common symptoms of COVID-19, so COVID-19 needs to be considered in differential diagnoses of acute undifferentiated febrile illness.